1999
DOI: 10.1029/1999jd900077
|View full text |Cite
|
Sign up to set email alerts
|

Arctic lower tropospheric aerosol trends and composition at Alert, Canada: 1980–1995

Abstract: aerosol components are associated with lower tropospheric ozone depletion at polar sunrise. In autumn, aerosol iodine but not bromine has a secondary peak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
260
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(299 citation statements)
references
References 73 publications
37
260
2
Order By: Relevance
“…Bootstrapping analysis found little error associated with this factor. Furthermore, similar marine factors have been observed in previous apportionment studies of Arctic snow (Hegg et al, 2009(Hegg et al, , 2010 and Arctic aerosol (Sirois and Barrie, 1999;Nguyen et al, 2013). …”
Section: Factor 1: Sea Saltsupporting
confidence: 61%
See 2 more Smart Citations
“…Bootstrapping analysis found little error associated with this factor. Furthermore, similar marine factors have been observed in previous apportionment studies of Arctic snow (Hegg et al, 2009(Hegg et al, , 2010 and Arctic aerosol (Sirois and Barrie, 1999;Nguyen et al, 2013). …”
Section: Factor 1: Sea Saltsupporting
confidence: 61%
“…The seven-factor solution for this factor showed low levels of error according to the bootstrapping analysis. Similar factors have been observed in previous atmospheric apportionment studies (e.g., Sirois and Barrie, 1999;Nguyen et al, 2013) but typically were not seen to account for such a large percentage of these metals, i.e., with loadings of 25-60 % m/m for major crustal analytes. This might suggest that a separate source was missed by this study, though this seems unlikely given the consistency of the observed factor.…”
Section: Factor 2: Crustal Metalssupporting
confidence: 61%
See 1 more Smart Citation
“…The atmosphere is the fastest and most direct route from the source of pollution: transport from the sources to the Arctic occurs in a matter of days or weeks (Pfirman et al, 1995;AMAP, 1997;Macdonald et al, 2000). *Corresponding author. Numerous studies have shown that aerosols in the Arctic are important for atmospheric chemistry and climate (Rahn, 1981;Barrie, 1986Barrie, , 1996Pacyna, 1991;Leck et al, 1996;Sirois and Barrie, 1999;Bigg and Leck, 2001). There is much evidence that atmospheric inputs contribute significantly to the chemical budget of marine areas (Duce et al, 1991;Lisitzin, 1996), but in the Arctic their role is underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of the month of February is motivated by two factors that favour the DGF: cold temperature and high concentration of acidic aerosols (Sirois and Barrie, 1999). 1D simulations have also shown that the DGF is the strongest in February .…”
Section: Design Of the Experimentsmentioning
confidence: 99%